Pengaruh Limbah Cair terhadap Kualitas Air dan Penyakit yang Timbul di Masyarakat Kelurahan Sei. Merbau Kecamatan Teluk Nibung Kota Tanjungbalai - Mulkan Iskandar Nasution; Riko Syahputra Manik; Witya Chairinda Sitorus; Uswatun Hasanah4; M. Ripanza Butar-butar (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Water is a source of life for the community and is a basic need that is used by the community every day for their daily needs. However, due to the increasingly dense population and the number of PT in Sei Merbau Village, Teluk Nibung District, the water is polluted by Liquid Waste. And people in Sei Merbau Village, Teluk Nibung District, feel the impact of the water such as water that is not suitable for consumption and the emergence of various diseases. This study aims to find out how the effect of liquid waste on water quality and diseases that arise in the community in Sei Village. Merbau, Teluk Nibung District. The research method used is descriptive qualitative research method in which data collection is carried out using interviews and field observations of 10 respondents aged between 25 - 40 years. The results of this study indicate that liquid waste causes changes in water quality and causes various skin diseases to occur in the community in Sei Village. Merbau, Teluk Nibung District. Keywords: Water, Liquid Waste, Society, Disease and Sei Merbau